Effect of Roasting and Brewing on the Antioxidant and Antiproliferative Activities of Tartary Buckwheat - Ji-yeon Ryu; Yoonseong Choi; Kun-Hwa Hong; Yong Suk Chung; Somi Kim Cho (Foods, 2020)
We evaluated the effect of the roasting and brewing conditions of Tartary buckwheat (TB), which is widely used in infusion teas, on its antioxidant and antiproliferative activities in vitro. TB was roasted at 210 °C for 10 min and brewed at a high temperature for a short time (HTST; 85–90 °C, 3 min) or at room temperature for a long time (RTLT; 25–30 °C, 24 h). Roasted TB (RTB) tea brewed at RTLT had the highest total polyphenol content (TPC) and total flavonoid content (TFC) among the four TB teas for different roasting and brewing conditions. Moreover, RTB brewed at RTLT showed the greatest 2,2-diphenyl-1-picrylhydrazyl-, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)-, and alkyl-scavenging activities. The TB tea brewed at RTLT had higher Fe2+-chelating activity than that brewed at HTST, irrespective of roasting. Moreover, RTB tea brewed at RTLT inhibited the proliferation of human pancreatic and breast cancer cells. Overall, RTB-RTLT displayed the largest effect on antioxidant and antiproliferative effects. Finally, rutin was found to possess the most pronounced effect on the antioxidant and antiproliferative activities of the TB teas. These results indicate that the antioxidant and antiproliferative activities of RTB are enhanced by RTLT brewing.